A study using black physically disabled women leaders' experiences to examine how a developmental state can deal with economic disparities faced by black young physically disabled women - Sipuka, Olwethu (Department of Health and Rehabilitation Sciences, 2015)
Includes abstract.~Includes bibliographical references (leaves 62-67).